The handbook of international school psychology - Jimerson, Shane R.; Oakland, Thomas; Farrell, Peter (Peter T.) (Sage Publications, 2007)
With contributions from authors from more than 40 countries 'The Handbook of International School Psychology' provides a description of the speciality of psychology devoted to the provision of services to children and youth, their teachers, and parents around the world.